Perancangan Website Preloved - Sari, Rani Indah; Simanjuntak, Yesy; Niska, Debi Yandra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The emergence of the trend to purchase preloved items as a cost-effective alternative to meet needs, particularly among students and young people, is driven by a sustainable lifestyle. The aim of this study is to develop a web based application that is easy to use, secure, and cost-efficient for managing and purchasing second-hand goods. To support the application design, data collection methods were employed through observations of similar platforms and literature reviews.These features include the ability for sellers to upload items, for buyers to search and purchase goods, and a review and rating system. To ensure that transaction processes run smoothly and are well-organized, a database design was developed. This application not only provides practical solutions for users but also contributes to reducing waste from the fashion industry, supporting a modern lifestyle.